Left ventricular function in relation to chronic residential air pollution in a general population. (September 2017) - Yang, Wen-Yi; Zhang, Zhen-Yu; Thijs, Lutgarde; Bijnens, Esmée M; Janssen, Bram G; Vanpoucke, Charlotte; Lefebvre, Wouter; Cauwenberghs, Nicholas; Wei, Fang-Fei; Luttun, Aernout; Verhamme, Peter; Van Hecke, Etienne; et al.
Background: In view of the increasing heart failure epidemic and awareness of the adverse impact of environmental pollution on human health, we investigated the association of left ventricular structure and function with air pollutants in a general population. Methods: In 671 randomly recruited Flemish (51.7% women; mean age, 50.4 years) we echocardiographically assessed left ventricular systolic strain and strain rate and the early and late peak velocities of transmitral blood flow and mitral annular movement (2005−2009). Using subject-level data, left ventricular function was cross-sectionally correlated with residential long-term exposure to air pollutants, including black carbon, PM2.5, PM10 (particulate matter) and nitrogen dioxide (NO2), while accounting for clustering by residential address and confounders. Results: Annual exposures to black carbon, PM2.5, PM10 and NO2 averaged 1.19, 13.0, 17.7, and 16.8 µg/m 3 . Systolic left ventricular function was worse ( p ≤ 0.027) with higher black carbon, PM2.5, PM10 and NO2 with association sizes per interquartile interval increment ranging from −0.339 to −0.458% for longitudinal strain and from −0.033 to −0.049 s −1 for longitudinal strain rate. Mitral E and a′ peak velocities were lower ( p ≤ 0.021) with higher black carbon, PM2.5 and PM10 with association sizes ranging from −1.727 to −1.947 cm/s and from −0.175 to −0.235 cm/s, respectively. In the geographic analysis, the systolic longitudinal strain sided with gradients in air pollution. The path analysis identified systemic inflammation as a possible mediator of associations with black carbon. Conclusions: Long-term low-level air pollution is associated with subclinical impairment of left ventricular performance and might be a risk factor for heart failure.